2020
DOI: 10.1101/2020.12.06.413849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Starvation induces shrinkage of the bacterial cytoplasm

Abstract: Environmental fluctuations are a common challenge for single-celled organisms; enteric bacteria such as Escherichia coli experience dramatic changes in nutrient availability, pH, and temperature during their journey into and out of the host. While the effects of altered nutrient availability on gene expression and protein synthesis are well known, their impacts on cytoplasmic dynamics and cell morphology have been largely overlooked. Here, we discover that depletion of utilizable nutrients results in shrinkage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Certain of the dynamics observed by Shi et al (2021) [37] are consistent with our observations, however, some observations are difficult to reconcile with experimental details and the known biology of pyoverdin. For example, polarization of mCherry occurred in the periplasm of E. coli soon after starvation, but these cells maintained high ATP levels typical of exponentially growing cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Certain of the dynamics observed by Shi et al (2021) [37] are consistent with our observations, however, some observations are difficult to reconcile with experimental details and the known biology of pyoverdin. For example, polarization of mCherry occurred in the periplasm of E. coli soon after starvation, but these cells maintained high ATP levels typical of exponentially growing cells.…”
Section: Discussionsupporting
confidence: 89%
“…Lack of location specificity hints at a connection to more general biophysical aspects of cell biology. Interestingly, a recent study of E. coli under starvation conditions showed polar accumulation of fluorescent markers, including mCherry [37]. Accumulation was connected to shrinkage of the cytoplasm, with shrinkage creating additional space in the polar region of the periplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Upon introduction to artificial fresh water, the bacteria morphologically change, most notably by increasing distance between the inner and the outer membrane. Dehiscence within bacteria, including V. cholerae, has previously been described and it has been associated with the transition to viable but non-culturable states, in which cells have a very low metabolic activity (Brenzinger et al, 2019;Shi et al, 2021). As noted in previous research, V. cholerae also expresses unknown structures in response to stressful environments (Dobro et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
“…How are V. cholerae cells able to thrive during these drastic changes in environmental conditions of the infection process? Previous studies have shown that the cells alter their shape in response to changing environments (Bartlett et al, 2017;Brenzinger et al, 2019;Shi et al, 2021). In addition to its shape, V. cholerae may also adapt its molecular machines, altering their availability and quantity, to levels that support success in the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting changes in gross morphology have the potential to impact transcription during the growth arrest that follows the completion of the reductive divisions, because the DNA becomes denser and more compacted even though the nucleoid occupies a slightly greater fraction of the cellular volume as growth rates slow toward growth arrest [30,31]. Recent studies have suggested that nutrient downshift can result in a modest decrease in cytoplasmic volume even in the absence of reductive divisions, leading to a further increase in cellular density [32]. Similar phenomena have also been observed in eukaryotic microbes such as yeast and have been proposed in both systems to contribute to increased macromolecular crowding, decreased mobility, and increased rigidity of both the chromosome(s) and the cytoplasm [33,34].…”
Section: The Transcriptional Challenges Of Growth Arrestmentioning
confidence: 99%